‘An Instrument of Reason’: William Scott’s logical poetics - Hetherington, M (Oxford University Press, 2015)
William Scott’s The Model of Poesy is a newly recovered work of late Elizabethan poetics. Among its most significant contributions to our understanding of the nature of literary theory at the end of the sixteenth century is its explicit debt to contemporary logic. It uses the normative tools of late humanist pedagogy and philosophy to construct a clear, well ordered and rule-based poetics, filling a gap in the field which had been explicitly if playfully acknowledged by other theorists of English poesy. This essay establishes Scott’s logical techniques, discussing analogues and, where possible, sources for his approach, focusing particularly on evidence for the influence of contemporary neo-Aristotelianism, as well as the mainstream logical teaching associated with figures like Philipp Melanchthon and John Seton. The essay argues that Scott’s logic conditioned his literary theory in productive ways, forcing him to think about the nature of artistic skill and prompting him to articulate a compelling account of poetic creativity. The Model emerges from a particular phase of intellectual and literary culture at the turn of the seventeenth century. If we pay careful attention to its mediation of that culture, it promises to enlarge our understanding of the literary world inhabited by Jonson, Shakespeare, and Scott’s peers at the Inns of Court.